Mitigation of greenhouse gas emissions and reduced irrigation water use in rice production through water-saving irrigation scheduling, reduced tillage and fertiliser application strategies - Islam, Syed Faiz-ul; Sander, Björn Ole; Quilty, James R; Neergaard, Andreas de; Groenigen, Jan Willem van; Jensen, Lars Stoumann (Elsevier, 2020)
Rice production systems are the largest anthropogenic wetlands on earth and feed more than half of the world's population. However, they are also a major source of global anthropogenic greenhouse gas (GHG) emissions. Several agronomic strategies have been proposed to improve water-use efficiency and reduce GHG emissions. The aim of this study was to evaluate the impact of water-saving irrigation (alternate wetting and drying (AWD) vs. soil water potential (SWP)), contrasting land establishment (puddling vs. reduced tillage) and fertiliser application methods (broadcast vs. liquid fertilisation) on water-use efficiency, GHG emissions and rice yield. The experiment was laid out in a randomised complete block design with eight treatments (all combinations of the three factors) and four replicates. AWD combined with broadcasting fertilisation was superior to SWP in terms of maintaining yield. However, seasonal nitrous oxide (N2O) emissions were significantly reduced by 64% and 66% in the Broadcast-SWP and Liquid fertiliser-SWP treatments, respectively, compared to corresponding treatments in AWD. The SWP also significantly reduced seasonal methane (CH4) emissions by 34 and 30% in the broadcast and liquid fertilisation treatments, respectively. Area-scaled GWPs were reduced by 48% and 54% in Broadcast-SWP and Liquid fertiliser-SWP treatments respectively compared to the corresponding treatments in AWD. Compared to AWD, the broadcast and liquid fertilisation in SWP irrigation treatments reduced yield-scaled GWPs by 46% and 37%, respectively. In terms of suitability, based on yield-scaled GWPs, the treatments can be ordered as follows: Broadcast-SWP < Broadcast-AWD = Liquid fertiliser-SWP < Liquid fertiliser-AWD. Growing-season water use was 15% lower in the SWP treatments compared with the water-saving AWD. Reduced tillage reduced additional water use during land preparation. The conclusions of this study are that improved water management and timely coordination of N fertiliser with crop demand can reduce water use, N loss via N2O emissions, and CH4 emissions.